Implementasi Pendidikan Karakter dalam Mata Pelajaran Pendidikan Kewarganegaraan pada Siswa Sekolah Dasar - Irzal Anderson; Riana Sari (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
The purpose of this study is to describe the implementation of character education in civic education subjects in class VI SDN 20/1 Jembatan Mas, Pemayung sub-district. This research is descriptive qualitative, namely research that can reveal facts comprehensively about the implementation of character education in civic education subjects in Class VI Students of SD Negeri 20/1 Jembatan Mas, Pemayung District. The subjects of this study were 2 grade VI teachers SDN 20/1 Mas bridge Pemayung sub-district with data collection techniques through interviews, observation, distributing questionnaires and documentation of supporting data. The results of this study show a description of the Implementation of Character Education in Citizenship Education Subjects in Class VI Students of SD Negeri 20 / I Jembatan Mas, Pemayung Subdistrict which has been well implemented through the stages of planning and implementing learning, and solutions to obstacles in the implementation of character education in PKn subjects.